Rhomboedrische Netze aus Kugeln im Dreidimensionalen Euklidischen Raum - Padervinskas, V. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. В. Падервинскас. Ромбоэдрические сети из сфер в трехмерном евклидовом пространстве V. Padervinskas. Romboedriniai tinklai iš sferų trimatėje euklidinėje erdvėje